UPACARA TEING HANG KEPADA LELUHUR DALAM BUDAYA MANGGARARAI: (Tinjauan Antropologis-Teologis) - Selatang, Fabianus (IN VERITATE LUX, 2018)
This research aims to reveal the theological meaning of the "teing hang" ritual for ancestors in Manggarai culture. Using descriptive qualitative methods and an anthropological-theological approach, the author analyzes the structural aspects of the ceremonial text. The results of structural and textual analysis show that the text of the "teing hang" ceremony contains deep theology, every word spoken has theological meaning. Through this ceremony, the speaker invites the Manggarai people to understand the theology of death with symbolic meaning. The author uses an anthropological approach to understand the essence of the ceremony through knowledge of the Manggarai people's personalities. In general, research concludes that the "teing hang" ceremony is not a form of idolatry, dualism, or syncretism. This ceremony raised Manggarai people's awareness of life after death and that the relationship between the living (Musafir Church) and the dead (Jaya Church and Suffering Church) does not end with death. Dead people are considered intermediaries for prayers to Allah because of their superhuman status, but their role cannot be equated with that of a welfare.